1985
DOI: 10.1172/jci112078
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of liver glycogen repletion in vivo by nuclear magnetic resonance spectroscopy.

Abstract: In order to quantitate the pathways by which liver glycogen is repleted, we administered 11-'3Cjglucose by gavage into awake 24-h fasted rats and examined the labeling pattern of 'IC in hepatic glycogen. Two doses of i1-'3Cjglucose, 1 and 6 mg/g body wt, were given to examine whether differences in the plasma glucose concentration altered the metabolic pathways via which liver glycogen was replenished. After 1 and 3 h (high-dose group) and after 1 and 2 h (low-dose group), the animals were anesthetized and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(52 citation statements)
references
References 29 publications
(25 reference statements)
8
44
0
Order By: Relevance
“…The frozen samples were stored at Ϫ70°C for subsequent analysis. On the day of the assay, samples were powdered and the glycogen was extracted and purified as previously described (42). The cold glycogen concentrations were determined by acid hydrolysis and enzyme degradation using ␣-1,4,6-amyloglucosidase (43).…”
Section: Methodsmentioning
confidence: 99%
“…The frozen samples were stored at Ϫ70°C for subsequent analysis. On the day of the assay, samples were powdered and the glycogen was extracted and purified as previously described (42). The cold glycogen concentrations were determined by acid hydrolysis and enzyme degradation using ␣-1,4,6-amyloglucosidase (43).…”
Section: Methodsmentioning
confidence: 99%
“…There is increasing evidence that the majority ofhepatic glycogen repletion after an oral glucose load in rat and man occurs via a gluconeogenic process (1)(2)(3)(4)(5)(6)(7)(8). It has been hypothesized that lactate and alanine are the primary gluconeogenic precursors for glycogen formation (2,(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that lactate and alanine are the primary gluconeogenic precursors for glycogen formation (2,(4)(5)(6). In a previous study using nuclear magnetic resonance spectroscopy (NMR),' we estimated that a minimum of 10-28% of newly formed glycogen was derived from alanine/lactate (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3: a and c. Shulman et al reported that glycogen is directly synthesized from a gluconeogenesis substrate such as lactate and alanine as well as from glucose (26). The mechanism by which CP-91149 decreased plasma glucose with increasing hepatic glycogen content was not fully understood, but these results suggested that suppressing breakdown of glycogen synthesized from gluconeogenesis substrate might be one of the mechanisms.…”
Section: Discussionmentioning
confidence: 99%